Analisis Keberhasilan Implementasi Model Flipped Classroom dalam Pembelajaran Matematika Tingkat Perguruan Tinggi - Loria Wahyuni; Suhartini Salingkat; Rendi Hadian A. Tamagola; Hersiyati Palayukan; Irajuana Haidar; Joni Wilson Sitopu (Journal on Education, 2024)
The Flipped Classroom model has become an intriguing topic in the context of mathematics education at the tertiary level. This literature review article aims to analyze the success of implementing the Flipped Classroom model in mathematics education at the tertiary level by exploring influencing factors. In-depth literature review was conducted to identify patterns and trends in evaluating the success of this model, including challenges faced and recommendations for further development. The results indicate that technological readiness, teacher involvement, student engagement, institutional support, and continuous evaluation are key factors in the success of implementing the Flipped Classroom model. This article provides valuable insights for educators and researchers in designing and implementing effective teaching models in tertiary education.